Myristate-protein interactions in poliovirus: interactions of VP4 threonine 28 contribute to the structural conformation of assembly intermediates and the stability of assembled virions. - Moscufo, N (1992)
The VP4 capsid protein of poliovirus is N-terminally modified with myristic acid. Within the poliovirus structure, a hydrogen bond is observed between the myristate carbonyl and the hydroxyl side chain of threonine 28 of VP4. This interaction is between two fivefold symmetry-related copies of VP4 and is one of several myristoyl-mediated interactions that appears to structurally link the promoters within the pentamer subunit of the virus particle. Site-specific substitutions of the threonine residue were constructed to investigate the biological relevance of these myristate-protein interactions. Replacement of the threonine with glycine or lysine is lethal, generating nonviable viruses. Substitution with serine or valine led to viable viruses, but these mutants displayed anomalies during virus assembly. In addition, both assembled serine- and valine-substituted virion particles showed reduced infectivity and were more sensitive to thermal inactivation and antibody neutralization. Thus the threonine residue provides interactions necessary for efficient assembly of the virus and for virion stability.